Cross-field and parallel dynamics of SOL filaments in TCV. (1st September 2022) - Offeddu, N.; Han, W.; Theiler, C.; Golfinopoulos, T.; Terry, J.L.; Marmar, E.; Wüthrich, C.; Tsui, C.K.; de Oliveira, H.; Duval, B.P.; Galassi, D.; Oliveira, D.S.; et al.
Abstract: Using recently installed scrape-off layer diagnostics on the tokamak à configuration variable, we characterise the poloidal and parallel properties of turbulent filaments. We access both attached and detached divertor conditions across a wide range of core densities ( f G ∈ [0.09, 0.66]) in diverted L-mode plasma configurations. With a gas puff imaging (GPI) diagnostic at the outer midplane we observed filaments with a monotonic increase in radial velocity (from 390 m s −1 to 800 m s −1 ) and cross-field radii (from 8.5 mm to 13.4 mm) with increasing core density. Interpreting the filament behaviour in the context of the two-region model by Myra et al (2006 Phys. Plasmas 13 112502), we find that they populate the ideal-interchange regime ( C i ) in discharges at very low densities, and the resistive X ( RX )-point regime for all other discharges. The scaling of filament velocity versus size shows good agreement with this interpretation. These results are discussed and compared with previous probe-based measurements for similar conditions, which mostly placed filaments in TCV in the resistive ballooning ( RB ) regime (Tsui et al 2018 Phys. Plasmas 25 072506). In addition, for the first time in TCV, the parallel filament extension is studied by magnetically aligning the GPI measurements at the outboard midplane with a reciprocating probe in the divertor. In agreement with the filaments being in the ideal-interchange and the RX-point regimes, they are found to extend beyond the X-point into the outer divertor leg.